Evervac: phase I/II study of immunogenicity and safety of a new adjuvant-free TBE vaccine cultivated in Vero cell culture. Issue 9 (1st September 2020) - Vorovitch, Mikhail F.; Grishina, Karina G.; Volok, Viktor P.; Chernokhaeva, Liubov L.; Grishin, Konstantin V.; Karganova, Galina G.; Ishmukhametov, Aidar A.
ABSTRACT: Approximately 10, 000 cases of tick-borne encephalitis (TBE), a serious disease of the central nervous system caused by tick-borne encephalitis virus (TBEV), are registered worldwide every year. Vaccination against TBE remains the most essential measure of preventing the disease. Unlike available TBE vaccines, a new inactivated lyophilized candidate vaccine Evervac is produced in Vero continuous cell culture and its final formulation does not include aluminum-based adjuvants. To study the safety and immunogenicity of Evervac, healthy adults 18–60 y of age were immunized twice at 30-d intervals. The study was single-blind, randomized, comparative, controlled, and was conducted in TBE-endemic areas. The commercial lyophilized vaccine TBE-Moscow was used as a comparison treatment. The subjects were observed for incidence, severity, and duration of adverse reactions. It was shown that the severity of local and systemic reactions in the Evervac vaccine group was mild to moderate. There were no significant differences in the incidence of adverse reactions between the Evervac and TBE-Moscow vaccine groups. Immunization with Evervac produced a significant increase in geometric mean titer (GMT) of anti-TBEV antibodies in both initially seronegative and seropositive recipients. The seroconversion rate for the initially seronegative recipients was 69% (GMT = 1:214) after the first dose and reached 100% after the second dose. In these parameters, there were no significant differences between the study and control vaccine groups. Thus, the adjuvant-free Vero-based vaccine Evervac was well tolerated, had low reactogenicity, induced a pronounced immune response, and was overall non-inferior to the commercial adjuvanted TBE vaccine used as a control.